PENGARUH HARGA, LOKASI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MIXUE ICE CREAM AND TEA DI KOTA BANJARMASIN - Salwa Noor Azizah; Novia Nour Halisa; Nurul Wahyuni; Rizky Muslim Hidayat (Business Administration, FISIP ULM, 2024)
This study describes how the levels of price, location, product quality and purchasing decisions. In addition, this study also aims to examine the effect of price, location and product quality on purchasing decisions. The research location was chosen in Banjarmasin City. This research uses a quantitative approach. A sample of 100 respondents was selected by insidental sampling with data collection using a questionnaire and data analysis using multiple linear regression analysis assisted by IBM SPSS Statistic Version 26.0. The results showed that Price has a partially significant effect on the Purchase Decision of Mìxuě Ice Cream & Tea in Banjarmasin City, Location has a partially significant effect on the Purchase Decision of Mìxuě Ice Cream & Tea in Banjarmasin City, Product Quality has a partially significant effect on the Purchase Decision of Mìxuě Ice Cream & Tea in Banjarmasin City. Price, Location and Product Quality simultaneously have a significant effect on the Purchase Decision of Mìxuě Ice Cream & Tea in Banjarmasin City.